Michelle : a biography - Mundy, Liza (New York : Simon & Schuster, 2008)
Washington Post writer Liza Mundy paints a revealing and intimate portrait of the most dynamic couple in politics today: Michelle, the highly organized, sometimes intimidating, list-making pragmatist; and Barack, the introspective political charmer who shoots for the stars. Michelle's story carries all the achievements and lingering pain of the post-civil rights era. She grew up on the south side of Chicago, in a neighborhood rocked by white flight. She went to Harvard Law School, became a corporate lawyer, then left to train community leaders. She can be funny and sharp-tongued, warm and blunt, empathic and demanding. Her relationship with Barack, like many couples with two careers and two children, has been strained at times by his political climb. In this carefully reported biography, drawing upon interviews with more than one hundred people, including one with Michelle herself, Mundy captures the complexity of this remarkable woman and the remarkable life she has lived.--From publisher description.
Includes bibliographical references (pages 201-217).
Keywords: Obama, Michelle, -- 1964-; African American women lawyers -- Biography